Changes of physiological tremor following maximum intensity exercise in male and female young swimmers - Gajewski, J.; Mazur-Rózycka, P.; Lach, P.; Rózycki, S.; Zmijewski, P.; Busko, K.; Michalski, R. (Human Movement, 2015)
Purpose. The aim of this study was to determine the changes in postural physiological tremor following maximum intensity effort performed on arm ergometer by young male and female swimmers. Methods. Ten female and nine male young swimmers served as subjects in the study. Forearm tremor was measured accelerometrically in the sitting position before the 30-second Wingate Anaerobic Test on arm ergometer and then 5, 15 and 30 minutes post-test. Results. Low-frequency tremor log-amplitude (L1-5) increased (repeated factor: p < 0.05) from -7.92 ± 0.45 to -7.44 ± 0.45 and from -6.81 ± 0.52 to -6.35 ± 0.58 in women and men, respectively (gender: p < 0.05) 5 minute post-test. Tremor log-amplitude (L15-20) increased (repeated factor: p < 0.001) from -9.26 ± 0.70 to -8.59 ± 0.61 and from -8.79 ± 0.65 to -8.39 ± 0.79 in women and men, respectively 5 minute post-test. No effect of gender was found for high frequency range.The increased tremor amplitude was observed even 30 minute post-exercise. Mean frequency of tremor spectra gradually decreased post-exercises (p < 0.001). Conclusions. Exercise-induced changes in tremor were similar in males and females. A fatigue produced a decrement in the mean frequency of tremor what suggested decreased muscle stiffness post-exercise. Such changes intremorafter exercise may be used as the indicator of fatigue in the nervous system.